An Analysis of Students' Language Errors in Scientific Discussions in the Indonesian Language Course in the Physical Education Study Program, Faculty of Sport Science and Public Health, Mandalika University of Education, Mataram - Supriadin Supriadin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe 1) language errors at the phonological level; 2) language errors at the morphological level. This study is descriptive in nature and uses a qualitative approach. The type of method used in this study is qualitative research. Data was selected using purposive sampling techniques. The object of this study was language errors made by students in scientific discussions in Indonesian language courses. Based on the research results, the author concludes that the total number of data found in the scientific discussions of second-semester students in the Physical Education Study Program, Faculty of Sports Science and Community Health, Physical Education Study Program, Mandalika University of Education, is 35 (phonological data) and 2 (morphological data). The phonological errors include: (1) Changes in vowel phonemes, where the phoneme /a/ is pronounced as /e/, the phoneme /i/ is pronounced as /e/, and the phoneme /e/ is pronounced as /i/; (2) Changes in consonant phonemes, namely the phoneme /f/ pronounced as /p/, the phoneme /p/ pronounced as /f/, the phoneme /v/ pronounced as /p/, and the phoneme /k/ pronounced as /c/; (3) Changes in vowel phonemes to consonant phonemes; (4) Changes in consonant phonemes to vowel phonemes. Meanwhile, morphological language errors include: (1) Omission of prefixes, namely, omission of the prefix meng-, omission of the prefix ber; (2) Replacement of morphemes, namely, the morpheme menge- is replaced by another morpheme, the morpheme be- is replaced by the morpheme ber-, the morpheme te-, replaced by the morpheme ter-.